(untitled) (Cadernos de Sociomuseologia, 2024)
Based on the current definition of museums presented by the International Council of Museums (2022) and key documents from the School of Thought in Sociomuseology, this article introduces the concept of Equitable Communication, illustrating it through a concrete example: a multi-format book developed for a Portuguese museum. This type of book is characterized by combining different ways of communicating a text within a single volume, integrating resources that include both children with and without disabilities, ensuring equal opportunities and allowing them to read together without barriers.The museum referenced here is Museu da Comunidade Concelhia da Batalha (MCCB), which many experts consider a benchmark in Portugal regarding accessibility, as it was planned and developed based on the principles of Universal Design. The results indicate that the development of a multi-format book by a museum is an act that strengthens its social function and role in social inclusion based on equal opportunities, as advocated by the School of Thought in Sociomuseology. Finally, it is pointed out that the multi-format book can be used in various ways, depending on the intended goal. Keywords: Equitable communication; accessibility in museums; multiformat book; Sociomuseology.